Changes of migraine aura with advancing age of patients - Adrian Scutelnic; Hristina Drangova; Antonia Klein; Nedelina Slavova; Morin Beyeler; Julian Lippert; Norbert Silimon; Thomas R. Meinel; Marcel Arnold; Urs Fischer; Franz Riederer; Heinrich P. Mattle; et al. (The Journal of Headache and Pain, 2023)
Abstract Aim Given the similar presentation of migraine aura and acute ischemic stroke, advancing patient age might change the characteristics of migraine with aura (MA) and be clinically important. Clinical data, however, are limited. Experimental studies indicate a decrease in the magnitude of cortical spreading depression (CSD), the pathophysiological correlate of migraine aura, with advancing age. Our study aimed to assess the influence of age on the clinical features of MA. Methods Three hundred and forty-three patients were interviewed using a structured questionnaire. The questions covered the headache characteristics and symptom types including the characteristics of the C-criterion, as defined by the International Classification of Headache Disorders 3rd Edition. The association of age with MA characteristics was assessed. Results The median age was 29 (IQR 28–52) and 235 of the 343 patients were women (69%). Individual symptoms of the C-criterion such as gradual aura spreading over longer than 5 min (P < 0.001), two or more aura symptoms occurring in succession (P = 0.005), duration of at least one MA symptom for longer than 60 min (P = 0.004), and associated headache (P = 0.01) were more frequent in younger patients. The number of symptoms (P = 0.003) including the C-characteristics decreased with increasing age (P < 0.027). Patients with sensory (P < 0.001), motor (P = 0.04) and speech disturbance (P = 0.02) were younger, and older patients with headache had less photophobia (P = 0.04) and phonophobia (P = 0.03). Sensitivity analyses yielded similar results. Conclusion The frequency of typical characteristics of migraine aura and migraine headache including photophobia and phonophobia decreases with advancing patient age. This might have potentially difficult implications for the diagnosis of MA in the elderly.